BAHASA GAUL SEBAGAI STRATEGI KOMUNIKASI INTERAKTIF DALAM SINIAR DEDDY CORBUZIER: KAJIAN PRAGMATIK - Shandy Shofary; Encep Suherman; Ninah Hasanah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines the use of slang language as an interactive communication strategy in Deddy Corbuzier’s podcast from a media pragmatics perspective. The study aims to describe the forms of slang language and explain its role in supporting communication within digital media. This research employed a qualitative descriptive method. The data consisted of utterances containing slang expressions in the podcast episode entitled “REZA: VIDI, KAMU DIEM DULU!! AKU DARAH TINGGI INI” published in November 2025. Data were collected through observation and note-taking techniques and analyzed using the interactive model of Miles and Huberman, including data reduction, data display, and conclusion drawing. The findings reveal that slang language appears in various forms, including non-standard words, Indonesian–English code-mixing, popular expressions, and spontaneous emotional utterances. The use of slang functions not only as an informal language variety but also as a communication strategy that facilitates information exchange, strengthens audience engagement, builds social closeness, and supports emotional expression among participants. Furthermore, slang language contributes to creating a more relaxed, interactive, and contextual communication atmosphere. These findings indicate that slang language has become an important element of digital communication practices and plays a significant role in shaping communication patterns in contemporary podcast media.